REINTEGRASI TRADISI ISLAM DAN ILMU SOSIAL-HUMANIORA (KOMPARASI RISET KOMUNIKASI ISLAM DAN KAJIAN SEJARAH) - Abdul Halik (Ilmu Komunikasi UIN Alauddin Makassar, 2019)
Communication science is a social science that reveals social reality (communication phenomena) with various perspectives. Historical studies are referred to as humanioran scientific scholars. The science of communication and history are both trying to express the meanings stored in the signs used by humans to interact. History offers the main aspects of human life and is represented through communication symbols. Through these symbols, humans can recognize and understand the past, detect the present, and anticipate the future. These symbols are constructed by convention by historical actors as identities that talk about many things. Social-humanities sciences such as communication and historical studies can be jointly developed through adaptation of more open methodologies so that they can be mutually reinforcing, both scientifically and for practical purposes. To be more comprehensive and integrative, the social-humanities sciences are also always encouraged to use the perspective of the tradition of Islamic scientific discipline.